Effect of Internal Resistance on Electric Current in a Closed Circuit (International Journal of Innovative Research in Computer Science & Technology, 2023)
The research aims to determine the effect of  internal resistance on electric current in a closed circuit. The  Sample of this study of 20 sample variation.The research  method used was the ex post facto method, by not providing  treatment but directly conducting related evaluations. Data  analysis technique used is by regression analysis. From the  results of the analysis it was found that Freghitung= 4.282  and Freg-table = 4.130 (Freg-count > Freg-table), so the  conclusion of this study is that there is a very large effect of  internal resistance on electric current in a closed circuit.
Keywords: Internal Resistance; Electric Current; Closed Circuit